Beauty of symmetry - The impact of logo symmetry on perceived product quality. - Xianghu Wu (PLoS ONE)
In an era of intense brand competition, a successful logo can effectively boost consumer awareness of a company. However, existing research has not thoroughly examined the aspect of symmetry in logo design. Addressing this gap, the present study investigates the impact of logo symmetry on consumers' perceived product quality. Through three online experiments, the results revealed that symmetrical logos significantly enhance perceived product quality compared to asymmetrical logos, with perceived stability mediating this effect. Furthermore, the study confirmed the moderating role of cognitive load, showing that symmetrical logos positively affect perceived product quality only under low cognitive load, while this effect vanishes under high cognitive load. This study contributes to the field of visual logo design and provides practical insights for companies in product promotion and logo design.